2013
DOI: 10.1186/2050-6511-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics and pharmacodynamics of remogliflozin etabonate, a novel SGLT2 inhibitor, and metformin when co-administered in subjects with type 2 diabetes mellitus

Abstract: BackgroundThe sodium-dependent glucose co-transporter-2 (SGLT2) is expressed in absorptive epithelia of the renal tubules. Remogliflozin etabonate (RE) is the prodrug of remogliflozin, the active entity that inhibits SGLT2. An inhibitor of this pathway would enhance urinary glucose excretion (UGE), and potentially improve plasma glucose concentrations in diabetic patients. RE is intended for use for the treatment of type 2 diabetes mellitus (T2DM) as monotherapy and in combination with existing therapies. Metf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
1
29
1
Order By: Relevance
“…In contrast to the findings for twice‐daily dosing in the present study, no significant changes in LDL cholesterol were observed for once‐daily dosing with RE . The major difference between the present study and that by Sykes et al is the dosing regimen and overnight inhibition of SGLT2 by the twice‐daily dosing. An ongoing hypothesis is that overnight inhibition of SGLT2 occurs with either the twice‐daily RE or with the long half‐life SGLT2 inhibitors, such as dapagliflozin and canagliflozin.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings for twice‐daily dosing in the present study, no significant changes in LDL cholesterol were observed for once‐daily dosing with RE . The major difference between the present study and that by Sykes et al is the dosing regimen and overnight inhibition of SGLT2 by the twice‐daily dosing. An ongoing hypothesis is that overnight inhibition of SGLT2 occurs with either the twice‐daily RE or with the long half‐life SGLT2 inhibitors, such as dapagliflozin and canagliflozin.…”
Section: Discussioncontrasting
confidence: 99%
“…Digital images were obtained by phosphorimaging. Abbreviations: bf-brown fat; ed-epdidymis; Hd-harderian gland; nm-nasal mucosa; pg-preputial gland; pr-prostate; sg-salivary gland; skn-non-pigmented skin; skp-pigmented skin; sv-seminal vesicles; ts-testis pharmacokinetic or dynamic interaction between these two anti-diabetic medicines [32]. Similarly, there are a number of expected coadministered drugs such as simvastatin, rosiglitazone and glimepiride that undergo extensive CYP-mediated metabolism [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Further the response was less than 20% of the response of rifampicin, an inducer of both CYP2B6 and 3A4. Overall, the CYP inhibition and induction data, along with the clinical observations to date [14,32], suggest that remogliflozin etabonate can be dosed with other drugs metabolized by CYP enzymes such as sulfonylureas, calcium channel blockers and statins without concern of a pharmacokinetic drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The LSS model was further validated using data from 16 previously published studies . The results (Table , Figure , Supplementary Figures S7 and S8) indicated that the AUC(0,24 h) predicted by the two point LSS model was in excellent agreement ( r 2 = 0.976, bias −1.0%, precision 4.3%) with the corresponding AUC(0,24 h) best estimates, over a wide range (3.8–22.4 μg h l −1 ) of AUC(0,24 h) values and under a variety of demographic, experimental and clinical conditions.…”
Section: Resultsmentioning
confidence: 81%